ANTIOXIDANT, HEMOLYTIC AND MUTAGENIC POTENTIAL OF PSORALEA CORYLIFOLIA - S. Khan; T. Iqbal; N. Ahmed; A. Jamil (Journal of Animal and Plant Sciences, 2015)
Plants are one of the natural sources of bioactive molecules with potential abilities against different stress conditions. During pathogenic exposure, an array of biologically active molecules like reactive oxygen intermediates, phytoalexins and defense peptides are synthesized as measure of plant resistance to combat the intensifying conditions. Such molecules play a key role in advancement in potential therapeutics development. Psoralea corylifolia (P. corylifolia), a medicinal herb was evaluated under fungal stress and normal conditions for its inherent bioactive potential. Under fungal stress plant protein/peptide extracts showed greater antioxidant potential evaluated by DPPH radical scavenging activity assay. Mutagenicity of the extracts showed that the plant was safe to use. Hemolytic activity assay exhibited increased percentage in induced seedling extracts that instigates possible applications of extracts against cancer.
Keywords: Bioactive molecules; pathogenic; P. corylifolia; bioactive potential; proteins/peptides